"We are not ignorant": Transnational migrants' experiences of racialized securitization. (April 2019) - Ybarra, Megan
This paper examines the dynamics of racialized securitization for transnational migrants across multiple borders—from Central America toward Mexico and the United States. Rather than a singular process where US policies, funding, and attitudes toward border security direct Mexican immigration enforcement, I argue that Mexican state collaboration redirects US xenophobia away from Mexican migrants and toward Central American migrants. Migrants' testimonies point to the ways that US and Mexican discourses are mobilized in different—but complementary—ways that shape them as racialized subjects with differential life chances. This is clearest through a crude mapping of people onto nationalities for deportation based on hair, language, and tattoos. Beyond legal violence, deported migrants describe their vulnerability as constructed within tacit networks of collaboration between actors in the US and Mexico, both licit and illicit, in an effort to extort migrants and their families. While race is a key signifier in border securitization, the differences between these racial states have material consequences in the differential state violence in immigration enforcement.